SYNTHESIS AND MAGNETIC PROPERTIES OF BINUCLEAR COMPLEX [N(n-C4H9)4][MnIIFeIII(ox)3] - Fahimah Martak; Hamzah Fansuri; Sekarayu Dianing Putri (Universitas Gadjah Mada, 2012)
Binuclear complex, [N(n-C4H9)4][MnIIFeIII(ox)3] (ox=oxalate), has been synthesized and characterized. Binuclear complex with formula of [N(n-C4H9)4][MnIIFeIII(ox)3] was synthesized by forming precursor K3[Fe(ox)3] which was followed by adding manganese chloride and tetrabutyl ammonium chloride. Characterization of the complex was made by microanalysis, FT-IR spectroscopy, x-ray diffraction and Magnetic Susceptibility Balance. Magnetic moment of binuclear complex [N(n-C4H9)4][MnIIFeIII(ox)3] is 7.81 BM. The compound has higher magnetic moment than the previously reported compound with different organic cation, [N(n-C5H11)4][MnIIFeIII(ox)3]. This behavior might be associated with the decreasing range among layers on polymeric network.